TV-Therapy: A Preliminary Theoretical Framework - MASTNAK WOLFGANG (Наука телевидения)
Broadly speaking, television is regarded as a mass media array providing information and entertainment. From a scientific perspective it also involves artistic features and counts as a highly influential socio-cultural phenomenon. While in this context also pathogenic and pathological aspects have been discussed and studied, health promoting and therapeutic factors of television are still greatly underrepresented in the realm of TV-sciences. On the basis of a random sample of qualitative data and meta-synthetic construction, the present article suggests a preliminary eight-dimensional theoretical framework of TV-therapy: (i) identity fusion and introjection, (ii) parallel worlds and escapism, (iii) subliminal mirroring and self-exploration, (iv) biographical work and self-integration, (v) therapeutic transference and creative coping, (vi) self-administration and self-regulation, (vii) social adjustment and virtual networking and (viii) TV as a source of topics and an incentive for people to communicate. Regarding psychodynamic impacts of television, the article encourages further studies on the interaction between television and individuals with mental conditions such as schizophrenia or eating disorders, as well as health-related TV-education. Television may become an important tool in public health, which calls television programme creators and television production companies into play.